The Effects of Injury Experiences on the Quality of Life in South Korean Adults Aged 20 Years or Over - Lee, Yoon-Ho; Park, Hae-Ryoung; Park, Sang-Sub (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to determine the effects of injury experiences on the quality of life. Injury can have a diversity of health-related effects, including activity restrictions, walking, and stress. This study used coded raw data. Methods/Statistical analysis: The raw data from “The Seventh Korea National Health and Nutrition Examination Survey(KNHANES Ⅶ-2)” were used. The surveys were the health survey, the physical examination survey, and the nutrition survey. Of these, the health survey was used as an instrument. EQ-5D in the health survey was used for the quality of life. Of 8,127 respondents, a total of 6,113 were included, with the exception of 2,014 aged <20 years who had system missing values. The analyses were carried out by using an SPSS 20.0 version program. Findings: EQ-5D was positively correlated with gender, age, subjective health status, and stress perception (p<.01). EQ-5D was negatively correlated with activity restrictions and injury experiences (p<.01). Activity restrictions (β=-.261, p<.001), followed by stress perception (β=-.095, p<.001) and injury experiences (β=-.058, p<.001), had the most negative affect EQ-5D. Improvements/Applications: Subjective health status, activity restrictions, and injury experiences were found to affect the quality of life. It is necessary to make institutional reinforcement for constant research and program development in pursuit of good life.